Disparities in Health Care for Black Patients in Physical Medicine and Rehabilitation in the United States: A Narrative Review. Issue 2 (5th December 2020) - Odonkor, Charles A.; Esparza, Rachel; Flores, Laura E.; Verduzco‐Gutierrez, Monica; Escalon, Miguel X.; Solinsky, Ryan; Silver, Julie K.
Abstract : Racial health disparities continue to disproportionately affect Black persons in the United States. Black individuals also have increased risk of worse outcomes associated with social determinants of health including socioeconomic factors such as income, education, and employment. This narrative review included studies originally spanning a period of approximately one decade (December 2009‐December 2019) from online databases and with subsequent updates though June 2020. The findings to date suggest pervasive inequities across common conditions and injuries in physical medicine and rehabilitation for this group compared to other racial/ethnic groups. We found health disparities across several domains for Black persons with stroke, traumatic brain injury, spinal cord injury, hip/knee osteoarthritis, and fractures, as well as cardiovascular and pulmonary disease. Although more research is needed, some contributing factors include low access to rehabilitation care, fewer referrals, lower utilization rates, perceived bias, and more self‐reliance, even after adjusting for hospital characteristics, age, disease severity, and relevant socioeconomic variables. Some studies found that Black individuals were less likely to receive care that was concordant with clinical guidelines per the reported literature. Our review highlights many gaps in the literature on racial disparities that are particularly notable in cardiac, pulmonary, and critical care rehabilitation. Clinicians, researchers, and policy makers should therefore consider race and ethnicity as important factors as we strive to optimize rehabilitation care for an increasingly diverse U.S. population.